Modulation of spontaneous and lipopolysaccharide-induced nitric oxide production and apoptosis by d-galactosamine in rat hepatocyte culture: the significance of combinations of different methods - Canová, Nikolina Kutinová; Martínek, Jindrich; Kmonícková, Eva; Zídek, Zdenek; Kameníková, Ludmila; Farghali, Hassan (Toxicology mechanisms and methods, 2008)
ABSTRACT Apoptotic markers and signals produced by xenobiotics as hepatotoxic D-galactosamine (D-GalN) and lipopolysaccharide (LPS) are extensively investigated in vivo. The contribution of various cells and factors as nitric oxide (NO) in mediating hepatocyte apoptosis in a rat model of systemic endotoxemia was reported. Therefore, the aim of the present work was to study the in vitro effect of D-GalN on nonstimulated or LPS-treated rat hepatocytes in culture and the potential involvement of NO in this process. Our results showed that the spontaneous and LPS-induced NO production was completely blocked by D-GalN during 0 to 24 hours. However, D-GalN slightly enhanced NO production during 24 to 48 hours. D-GalN was more potent to induce hepatocyte apoptosis and necrosis during 24 to 48 than 0 to 24 hours as evidenced morphologically (Annexin V/propidium iodide staining) and biochemically (caspase-3-like activity, alanine-aminotransferase leakage, MTT test). Interestingly, D-GalN treatment suppressed mitochondrial cytochrome C release throughout the study. LPS addition to D-GalN considerably aggravated apoptotic/necrotic markers only during 0 to 24 hours. Surprisingly, a share of apoptotic cells was distinctly lower after LPS + GalN treatment than after LPS alone during 0 to 24 hours, while 24- to 48-hour incubation produced massive apoptotic/necrotic hepatocytes. It may be concluded that there is a significant modulation of NO production by D-GalN. Because the role of NO is only partly decisive in the apoptotic/necrotic events, and considering the fraction of the cells completing apoptosis while others that turn toward necrosis (aponecrosis), caution should be exercised in apoptosis data interpretation and combinations of different test methods should be applied.